1999
DOI: 10.1177/000348949910800911
|View full text |Cite
|
Sign up to set email alerts
|

Management of Persistent Tracheocutaneous Fistula in the Pediatric Age Group

Abstract: Different surgical methods have been advocated for closure of persistent tracheocutaneous fistula (TCF) in children. The objective of this study was to compare different methods of repair and postoperative care that were used for management of TCF in children. The charts of 98 children with persistent TCF who were surgically managed in our department between January 1990 and April 1997 were reviewed retrospectively. Excision of the fistulous tract and healing by secondary intention was employed in 18 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 12 publications
0
55
1
Order By: Relevance
“…A variety of TCF closure techniques have been advocated and can be classified as primary closure in layers [13], primary closure with fistulectomy [2,7,14,16] and fistulectomy with closure by secondary intent [8,10,12,15]. Some authors argue that primary closure is associated with an unacceptable complication rate, opting instead for closure by secondary intention [3,8,10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of TCF closure techniques have been advocated and can be classified as primary closure in layers [13], primary closure with fistulectomy [2,7,14,16] and fistulectomy with closure by secondary intent [8,10,12,15]. Some authors argue that primary closure is associated with an unacceptable complication rate, opting instead for closure by secondary intention [3,8,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argue that primary closure is associated with an unacceptable complication rate, opting instead for closure by secondary intention [3,8,10,12]. Other authors cite low complication rates, improved cosmetic results and the ability to observe the patient in the hospital following immediate closure [2,7,13,14,16]. Our choice of closure technique, fistulectomy and primary closure in layers, has been guided by the specific anatomical design of the ''starplasty'' itself as well as by our uncomplicated experience with primary layered TCF closure following decannulation of children with standard tracheotomies.…”
Section: Discussionmentioning
confidence: 99%
“…Most techniques involve initial resection of the epithelialized tract. The wound can then be managed with dressing changes to promote healing by secondary intention 1,2,6 or by primary closure. Several techniques have been used to augment closure of the fistula, including mobilization and closure of the strap muscles over the trachea, 1,7 using the tract of the fistula as a component of the closure, 8 and performing a modified cutaneous Z‐plasty over the repaired tracheal defect.…”
Section: Discussionmentioning
confidence: 99%
“…However, a review of 98 pediatric patients with persistent TCF revealed no difference in postoperative complications between primary closure and healing by secondary intention. 2 …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] We have previously compared the 2 methods of TCF closure at our institution and found no significant differences in risks or efficacy between primary closure and secondary intention. 9 Shortly after this study was published, we experienced 2 serious complications using the primary closure method. This prompted a gradual cultural shift in our Division toward the secondary intention method.…”
mentioning
confidence: 99%